Smart Accıdent Detectıon and Traffıc Alertıng System - Erram Nikhitha Patel, Pannala Sowmya Reddy, Dr. Deepika Vodnala (International Journal of Advanced Science and Technology, 2020)
Presently majority of the accidents occurring because of an expansion in populace, which prompts increment in the use of vehicles drastically. The significant foundations for accidents are carelessness of the individual who is driving the vehicle with high speed, drunk and drive, over stress, and so on. Once accident happens, at that point huge issue is arriving at the specific spot, as a rule people will arrive at the spot after the significant misfortune occurred. To conquer this issue, we presented an IoT based system, which identifies the vehicular accidents and informing the rescue team immediately. The proposed framework is executed by coordinating smart sensor with microcontroller inside the vehicle which can trigger by the time of accident. Along with this GPS and GSM modules are interfaced to obtain the location of the accidents and send an alert message to the enrolled numbers to indicate them about the accident and to get quick help at the area.Keywords: Arduino Uno, GSM Module, Micro- electro mechanical sensor, Accident detection